A voz e o corpo: linguagem, estética e complexidade para uma reflexão no teatro de Antonin Artaud - Edson Fernandes (EccoS – Revista Científica)
This article intends to reflect on the voice and the body, as being both esthetics and language as well as communications constituents, yet emphasizing the discussion about the corporeality and the vocallity as being the representation of mythical, symbolical and ritualistic narratives. Simultaneously, it tries to understand the dimensions of the semiotic complexity of both the gesture and the verb from the Artaudians theatrical experience. Particularlly, at this point, the orallity is discussed on the Paul Zumthors work in which its development is fully performatic pushed and reflected in the communication process, under the sociocultural and esthetical perspectives, since it searches for a dialogue between the subjects voice and body language. Finally, it establishes a reflection on not only the play of being present and absent, at the same time, but also on the definition and indefinition of the esthetical field, in which the body and the voice encode their own experiences.